Voyage to utopias : a fictional guide through social philosophy - Fitzpatrick, Tony, 1966- (Bristol ; Portland, OR : Policy Press, 2010)
This fictional account introduces the reader to key to key ideas on social and political philosophy. It provides them with the key skills of philosophical investigation in a rigorous, yet accessible way. The novel is comical, informative and entertaining, allowing students to experience often complex ideas from the inside.
Includes bibliographical references.
Keywords: Utopias; Social justice; Sociology -- Philosophy; Utopias -- Fiction; Social justice -- Fiction; Sociology -- Philosophy -- Fiction